2019
DOI: 10.3201/eid2510.181408
|View full text |Cite
|
Sign up to set email alerts
|

Risk for Invasive Streptococcal Infections among Adults Experiencing Homelessness, Anchorage, Alaska, USA, 2002–2015

Abstract: The risk for invasive streptococcal infection has not been clearly quantified among persons experiencing homelessness (PEH). We compared the incidence of detected cases of invasive group A Streptococcus infection, group B Streptococcus infection, and Streptococcus pneumoniae (pneumococcal) infection among PEH with that among the general population in Anchorage, Alaska, USA, during 2002–2015. We used data from the Centers for Disease Control and Prevention’s Arctic Investigations Program surveillance system, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…Thirteen studies concerning pneumococcal infections in homeless people were retrieved between 1988 and 2017 (including one unpublished data set) [2, 68-78]: 12 studies were conducted in adults (mean age: 19-54 years, range 16-78 years) and one in a population comprising children and adults (mean age: 42 years, range 0-90 years). Most studies were conducted in Canada (n=8) [68, 70-76], followed by France (n=3, including one unpublished data set) [2, 78], and the USA (n=2) [69, 77]. Two molecular prevalence surveys reported rates of 12.4% and 15.5% for pneumococcal nasopharyngeal carriage among a total of 575 sheltered homeless persons in Marseille, France between 2015-2018 (including one unpublished data set) [2], and prevalence was positively associated with respiratory symptoms and signs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirteen studies concerning pneumococcal infections in homeless people were retrieved between 1988 and 2017 (including one unpublished data set) [2, 68-78]: 12 studies were conducted in adults (mean age: 19-54 years, range 16-78 years) and one in a population comprising children and adults (mean age: 42 years, range 0-90 years). Most studies were conducted in Canada (n=8) [68, 70-76], followed by France (n=3, including one unpublished data set) [2, 78], and the USA (n=2) [69, 77]. Two molecular prevalence surveys reported rates of 12.4% and 15.5% for pneumococcal nasopharyngeal carriage among a total of 575 sheltered homeless persons in Marseille, France between 2015-2018 (including one unpublished data set) [2], and prevalence was positively associated with respiratory symptoms and signs.…”
Section: Resultsmentioning
confidence: 99%
“…Two molecular prevalence surveys reported rates of 12.4% and 15.5% for pneumococcal nasopharyngeal carriage among a total of 575 sheltered homeless persons in Marseille, France between 2015-2018 (including one unpublished data set) [2], and prevalence was positively associated with respiratory symptoms and signs. Other studies described eleven outbreaks of invasive pneumococcal disease (IPD) occurring in different cities in Canada, the USA and France; of those, two studies reported 153 homeless individuals hospitalised with IPD, which accounted for 1.4%-8.4% of all homeless people present in two cities, Toronto (Canada) and Anchorage (USA) [76, 77]; nine other studies reported a high proportion (4.7%-48.8%) of homelessness among 4742 individuals hospitalised with IPD [68-75, 78]. Homeless individuals with IDP were typically younger [73, 77], more often male [73], smokers[73, 75, 76], alcohol abusers [73, 75, 77], illegal drug users [73, 75], and had a primary diagnosis of pneumonia [73], HIV infection or liver disease [76] when compared with non-homeless individuals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported incidence rates of ISD are increasing significantly in developed nations such as Canada and New Zealand [9,10]. Homelessness and other measures of disadvantage are significant risk factors [9][10][11]. Within developed countries, indigenous populations suffer some of the highest reported rates of ISD.…”
Section: Strep Amentioning
confidence: 99%
“…In comparison to the general population, people who are homeless experience poorer health and health-related outcomes. People who are homeless are at greater risk of developing a range of mental and physical illnesses, including vaccine-preventable diseases such as hepatitis (Hosseini & Ding, 2018;Noska et al, 2017;Peak et al, 2019), pneumococcal disease (Lemay et al, 2019;McKee et al, 2018;Mosites et al, 2019) and tuberculosis (Bamrah et al, 2013;Khan et al, 2011;Lee et al, 2013;Romaszko et al, 2013). Once ill, people who are homeless have a greater likelihood of hospitalisation, intensive care unit (ICU) admission, and death (Lewer et al, 2020).…”
Section: Health Disparities and Vaccine-preventable Diseases In Peoplmentioning
confidence: 99%